The Academic Vocabulary List in Linguistics for EFL University Students - Kim, Hyeon Okh; Lee, Hye Kyung (Korean Journal of English Language and Linguistics, 2019)
The study investigates the vocabulary loads of English-medium linguistics textbooks for EFL students at tertiary level and identifies a Linguistic Academic Vocabulary List (LAVL) in a way of promoting students’ academic literacy by enhancing lexical knowledge in English. For the purposes, the study developed a Linguistics Textbooks Corpus (LTC) containing 1,141,830 running words complied from five major linguistics textbooks used in the foundation courses for English majors. The results indicated the knowledge of the most frequent 7,000 word families in addition to proper nouns, interjections, abbreviations, glossary, and transparent compounds would be in need for 95% lexical coverage of a linguistics textbook written in English. Beyond the first 2,000 word lists covering up to 84.95%, the study further identified a list of 607 word families that correspond to 11.05% of the entire corpus of the linguistics textbooks. The study hopes to provide a way of assisting EFL university students in enriching their lexical competence to attain a reasonable level of understanding in the main textbooks, giving practical information and useful directions to ESP instructors and materials writers so that the EFL students could better benefit from focusing on the words of imminent need and relevance.
Keywords: academic vocabulary; EAP; EFL; linguistics word list; vocabulary load